Steamship Service to Alaska (1898) - Boston and Alaska Transportation Company (1898)
Go quickly, safely and direct to the Alaska Gold Fields.Owning the three fine sea-going steamers, unsurpassed on the coast, the Brixham, Laurada, and So. Portland, operated in connection with their new modern and light-draft River Steamers on the Yukon River, will maintain a regular line between Seattle and Alaska.A.E.Cronenwett, General Traffic Manager. Klondike Gold Rush Steamships, ferries and boats Transportation and communication